To evaluate the equation \( 6^{1/2} \cdot (\sqrt{6})^3 = 36 \), let's simplify each side step by step.
First, we know that:
\[ 6^{1/2} = \sqrt{6} \]
Next, we can rewrite \( (\sqrt{6})^3 \):
\[ (\sqrt{6})^3 = (6^{1/2})^3 = 6^{(1/2) \cdot 3} = 6^{3/2} \]
Now, we can substitute these into the left-hand side of the equation:
\[ \sqrt{6} \cdot (\sqrt{6})^3 = 6^{1/2} \cdot 6^{3/2} \]
Using the Product Property of exponents, which states \( a^m \cdot a^n = a^{m+n} \), we can add the exponents:
\[ 6^{1/2} \cdot 6^{3/2} = 6^{(1/2 + 3/2)} = 6^{4/2} = 6^2 \]
And since:
\[ 6^2 = 36 \]
So the equation:
\[ 6^{1/2} \cdot (\sqrt{6})^3 = 36 \]
is true.
Thus, the correct response is:
True, according to the Product Property.